State and Freedom by F. W. J. Schelling - Schmiljun, André (ETHICS IN PROGRESS, 2019)
This paper examines the two terms 'state' and 'freedom' in the work of F. W. J. Schelling. It will be argued that, although Schelling refuses the general role of state, criticizing it as 'mechanism', he accepts the fact that the state is the only guarantor - considered as 'second nature' – to restore the 'lost unit', to secure the freedom of men and to realize a 'Höheres Lebens'. For this purpose, Schelling uses powerful metaphors of the state as 'organism' and 'artwork', postulating his ideal of a political community.